2000
DOI: 10.1046/j.1462-2920.2000.00097.x
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and community structure within anoxic sediment from marine salinity meromictic lakes and a coastal meromictic marine basin, Vestfold Hills, Eastern Antarctica

Abstract: 16S rDNA clone library analysis was used to examine the biodiversity and community structure within anoxic sediments of several marine-type salinity meromictic lakes and a coastal marine basin located in the Vestfolds Hills area of Eastern Antarctica. From 69 to 130 (555 total) 16S rDNA clones were analysed from each sediment sample, and restriction fragment length polymorphism (RFLP) and sequence analysis grouped the clones into 202 distinct phylotypes (a clone group with sequence similarity of >0.98). A numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
110
1
3

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(122 citation statements)
references
References 40 publications
7
110
1
3
Order By: Relevance
“…Our results show that the prokaryotic diversity is comparable to, if not higher than, that shown in other studies of Antarctic meltwater lake sediments (Bowman et al 2000), microbial mats in East Antarctic lakes (Brambilla et al 2001), and the Arctic Ocean (Raven-schlag et al 1999), each of which report a high level of complexity in the prokaryotic community structure. The linearity of the rarefaction curve (Fig.…”
Section: Discussionsupporting
confidence: 87%
“…Our results show that the prokaryotic diversity is comparable to, if not higher than, that shown in other studies of Antarctic meltwater lake sediments (Bowman et al 2000), microbial mats in East Antarctic lakes (Brambilla et al 2001), and the Arctic Ocean (Raven-schlag et al 1999), each of which report a high level of complexity in the prokaryotic community structure. The linearity of the rarefaction curve (Fig.…”
Section: Discussionsupporting
confidence: 87%
“…Our data and those of Bowman et al (3) indicated that new distinct chlamydial lineages exist in natural environments as different as Antarctic marine salinity lake sediments and European freshwater ponds. All the chlamydiae described until now are able to infect vertebrates and to induce diseases : it may be of interest to estimate their prevalence and diversity in various natural habitats and in this way to identify possible sources of infections for both known and new chlamydiae.…”
Section: New Chlamydial Lineages From Freshwater Samplessupporting
confidence: 80%
“…Inoculation and determination of the number of cells associated with the seeds\roots was done as described (3,4). Results are the average of two assays where each data point corresponds to duplicate samples from three seedlings.…”
Section: Microbiology 148 February 2002 341mentioning
confidence: 99%
See 1 more Smart Citation
“…A molecular study using 16S rRNA gene clone library analysis examined the community structure of the anoxic sediments (Bowman et al 2000). Diversity in the sulphide-rich anoxic sediments was surprisingly high.…”
Section: The Anoxic Sedimentmentioning
confidence: 99%